2005
DOI: 10.1038/sj.cdd.4401787
|View full text |Cite
|
Sign up to set email alerts
|

EndoG is dispensable in embryogenesis and apoptosis

Abstract: The mitochondrial protein, endonuclease G (EndoG), is one of the endonucleases implicated in DNA fragmentation during apoptosis. It has been shown to translocate from the mitochondria to the nucleus upon cell death stimuli. These observations suggest that EndoG is a mitochondrial cell death effector, and that it possibly acts as a cell death nuclease, similar to DNA fragmentation factor. To better understand the role of EndoG in development and apoptosis, we generated EndoG null mice by homologous gene targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
84
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 38 publications
2
84
0
2
Order By: Relevance
“…A role of EndoG in apoptosis is somewhat controversial. EndoG knock-out mice have no defect in apoptotic DNA degradation (16,17), but this might be due to redundancy with CAD and additional nucleases (1,2,18). RNA interference experiments and genetic data in Saccharomyces cerevisiae support a role of EndoG in apoptosis (8,19,20).…”
mentioning
confidence: 85%
“…A role of EndoG in apoptosis is somewhat controversial. EndoG knock-out mice have no defect in apoptotic DNA degradation (16,17), but this might be due to redundancy with CAD and additional nucleases (1,2,18). RNA interference experiments and genetic data in Saccharomyces cerevisiae support a role of EndoG in apoptosis (8,19,20).…”
mentioning
confidence: 85%
“…75,76 These mechanisms present a considerable degree of redundancy, as demonstrated by the fact that the knockout or genetic inhibition of single IMS proteins not always affects the execution of intrinsic apoptosis. 77 Moreover, the relative contribution of these processes to intrinsic apoptosis varies in distinct physiological, pathological and experimental scenarios. Thus, while ENDOG appears to be dispensable for intrinsic apoptosis in mammalian models, 77 Nuc1p, the yeast ortholog of ENDOG, has an important role during the apoptotic response of Saccharomyces cerevisiae to chronological aging in non-fermentable carbon sources (which potentiate mitochondrial respiration).…”
Section: Functional Classification Of Cell Death Modalities L Galluzzmentioning
confidence: 99%
“…77 Moreover, the relative contribution of these processes to intrinsic apoptosis varies in distinct physiological, pathological and experimental scenarios. Thus, while ENDOG appears to be dispensable for intrinsic apoptosis in mammalian models, 77 Nuc1p, the yeast ortholog of ENDOG, has an important role during the apoptotic response of Saccharomyces cerevisiae to chronological aging in non-fermentable carbon sources (which potentiate mitochondrial respiration). 71 DRONC, the ortholog of caspase-9 in Drosophila melanogaster, is required for many forms of developmental cell deaths and apoptosis induced by DNA damage in vivo.…”
Section: Functional Classification Of Cell Death Modalities L Galluzzmentioning
confidence: 99%
“…Initially, Zhang et al showed that homozygous EndoGÀ/À KO mice are not viable, which supported the importance of this enzyme for apoptosis during early development. Later, Irvine et al 3 and then David et al 2 had independently developed viable EndoGÀ/À mouse knockouts. All three reports used mice of different backgrounds, which perhaps may explain the contradiction.…”
mentioning
confidence: 99%
“…In sharp contrast, EndoG had very little or no expression in adult spleen and in embryonic organs at the E13.5 stage. The leastdifferentiated mesenchymal cells, which are very often used for the isolation of embryonic fibroblasts and subsequent studies of cytotoxicity, 2,20 showed no detectable EndoG expression. Data presented in the NIH UniGene database (www.ncbi.nlm.nih.gov/UniGene) indirectly confirm that EndoG expression varies in different cell types, tissues and organs, and that embryos have very low (if any) expression of EndoG compared to adult organs.…”
mentioning
confidence: 99%